The Effectiveness of Using Wordwall Application on the Students’ Vocabulary Mastery at Junior High School - Daniar Nur Fadhillah; Marsuki (Universitas Insan Budi Utomo, 2026)
This study aimed to investigate the effectiveness of the Wordwall application in improving students’ vocabulary mastery at SMP Darul Fikar Al Latifi. This study employed a quantitative approach using a pre-experimental One-Group Pretest–Posttest Design. The participants were 20 eighth-grade students. Data were collected through a 20-item multiple-choice vocabulary test and analyzed using descriptive statistics, the Shapiro–Wilk normality test, and a Paired Sample t-test with SPSS version 26. The findings showed that the mean score increased from 72.50 in the pretest to 87.00 in the posttest. The Paired Sample t-test revealed a significance value of 0.000 (p < 0.05), indicating that the Wordwall application significantly improved students’ vocabulary mastery. Therefore, Wordwall can be considered an effective and engaging learning medium for teaching English vocabulary at the junior high school level.